Effects of decreasing phosphorus concentrations in diets and phytase supplementation on growth performance, stress response, and intestinal health in broiler chickens - Chayeong Lee; Hyun Woo Kim; Chan Ho Kwon; Gi Ppeum Han; Ji Hye Lee; Dong Yong Kil (Poultry Science)
The current study aimed to investigate the effect of decreasing P concentrations in diets and phytase supplementation on growth performance, stress response, and intestinal health in broiler chickens. A total of four hundred 8-d-old Ross broiler chicks were randomly allotted to 1 of 4 dietary treatments with 10 replicates. Three treatment diets were formulated to contain different concentrations of available P (aP): adequate P (0.44 % aP), low P (0.30 % aP), and very low P (0.10 % aP) levels. One additional diet was prepared by supplementing 1,000 FTU/kg phytase in very low-P diets to maintain its aP concentrations equal to those in low-P diets. The experiment lasted for 25 d. It was observed that growth performance and toe ash concentrations were decreased (P < 0.05) in birds fed very low-P diets compared with those fed other treatment diets. Birds fed very low-P diets exhibited a greater (P < 0.05) blood heterophil:lymphocyte ratio than those fed other treatment diets. Jejunal villus height in birds fed adequate P diets or low-P diets was greater (P < 0.05) than those fed very low-P diets or very low-P diets with phytase. The malondialdehyde concentrations in the jejunal mucosa were greater (P < 0.05) for very low-P treatment than for other treatments. The expression levels of IL-4 and OCLN in the jejunal mucosa were less (P < 0.05) for adequate P treatment than for low-P treatment and very low-P with phytase treatment. Expression levels of P transporter genes in the jejunal mucosa were not affected by dietary treatments. In conclusion, feeding very low-P diets impaired growth performance, bone development, and jejunal morphology in broiler chickens with elevated stress response and intestinal lipid peroxidation. However, feeding low-P diets or very low-P diets with phytase maintained bone development, stress response, and antioxidant status in broiler chickens. The gene expression of intestinal P transporters were not influenced by decreasing P concentrations in diets and phytase supplementation in very low-P diets under the current experimental condition.